Urban Water in Japan. - De Graaf, Rutger (Taylor & Francis Ltd., 2008)
In Japan, situated in a low-lying delta, half of the population and 75 per cent of the property are concentrated in flooding-vulnerable areas. This book treats the implementation of measures and management practices in Japan to realize climate robust sustainable urban water management.